Theory and Measurements of Bitumen Binders Adhesion to Aggregate - Remisova, Eva (Communications - Scientific letters of the University of Zilina, 2004)
The pavement as unit is able to perform services, provided that we ensure good synergy of layers and especially good adhesion between used materials. Adhesion knowledge allows to design suitable technology by preventing defects and to ensure service ability and life of pavement. In the paper there is a theoretical analysis of problem of bitumen binders adhesion to aggregate, basic methodologies to evaluate this property and specific results achieved at measuring by the method STN 65 7089 and EN 12272-3. At the same time the results are compared from the type of aggregate point of view as one of the most important factors that influenced adhesion.